An Experimental Reconstruction of Hair Colours from the Jin and Tang Dynasties (265-907 AD) in China - Bangcheng Tang; Yan Xue; Yijie Yan; Bo Yuan (EXARC Journal)
Hair colours, as a daily cosmetic used in ancient Chinese life, often appear in ancient Chinese medical books, according to types, and can be classified into herbal hair colours and mineral hair colours. Experimental reconstruction of herbal hair colours and mineral hair colours was carried out to explore the influence of factors such as the type and material of hair colours on the colouring effect. Meanwhile, the experiments were recorded and analysed using a stereo microscope. The experimental results show that the ancient hair colours are authentic and it is feasible that mineral hair colours and herbal hair colours are capable of colouring hair. Mineral hair colours have better colour fastness and colouring effects than herbal hair colours.